Forgery of Authentic Instruments by Notaries and the Scope of Legal Liability - Khadijah, Khadijah; Tarsono, Edi; Wuryandari, Utji Sri Wulan; Surono, Agus (Jurnal Ilmu Hukum Kyadiren, 2026)
The forgery of authentic deeds by notaries constitutes a serious legal issue with direct implications for legal certainty and public trust in the civil law system. As public officials, notaries are not only responsible for the formal accuracy of deeds but are also bound by a duty of care in verifying the identities and documents of the parties involved. This article examines the construction of notarial legal liability in cases of authentic deed forgery and the legal consequences arising from deeds executed on the basis of invalid document verification. Employing a normative legal approach, the study analyzes statutory regulations, legal doctrine, and judicial decisions, with particular emphasis on Bandung High Court Decision No. 73/Pid/2023/PT.BDG as a case study. The findings indicate that a notary’s failure to exercise due care, especially within the scope of official authority, may constitute fault giving rise to criminal, civil, and administrative liability. Authentic deeds prepared on the basis of invalid documentation may suffer a degradation of evidentiary value and may lead to the annulment of the legal acts embodied therein. The Bandung High Court decision affirms that the notary’s duty of care serves as a primary benchmark in assessing criminal liability, while also highlighting the need for clearer parameters to distinguish administrative negligence from criminal negligence in order to safeguard legal certainty.